Digital manufacturing for accelerating organ-on-a-chip dissemination and electrochemical biosensing integration. Issue 24 (7th November 2022) - Hernández-Rodríguez, Juan F.; López, Miguel Ángel; Rojas, Daniel; Escarpa, Alberto
Abstract : Digital manufacturing enables microfabrication of organ-on-a-chip and electrochemical microfluidic devices to be taken from sophisticated cleanroom facilities to conventional laboratories increasing the accessibility to both technologies. Abstract : Organ on-a-chip (OoC) is a promising technology that aims to recapitulate human body pathophysiology in a more precise way to advance in drug development and complex disease understanding. However, the presence of OoC in biological laboratories is still limited and mainly restricted to laboratories with access to cleanroom facilities. Besides, the current analytical methods employed to extract information from the organ models are endpoint and post facto assays which makes it difficult to ensure that during the biological experiment the cell microenvironment, cellular functionality and behaviour are controlled. Hence, the integration of real-time biosensors is highly needed and requested by the OoC end-user community to provide insight into organ function and responses to stimuli. In this context, electrochemical sensors stand out due to their advantageous features like miniaturization capabilities, ease of use, automatization and high sensitivity and selectivity. Electrochemical sensors have been already successfully miniaturized and employed in other fields such as wearables and point-of-care devices. We have identified that the explanation for this issue may be, to a large extent, the accessibility to microfabrication technologies. These fields employ preferably digital manufacturing (DM), which is a more accessible microfabrication approach regardless of funding and facilities. Therefore, we envision that a paradigm shift in microfabrication that adopts DM instead of the dominating soft lithography for the in-lab microfabrication of OoC devices will contribute to the dissemination of the field and integration of the promising real-time sensing.